Developing capacities for critical thinking and philosophical reasoning in schools - Hashim, Rosnani (Centre for Civilisational Dialogue, 2011)
Education deals with knowledge, skilis and values transmitted and further developed from man to man, culture to culture and civilisation to civilisation. Through education we are transformed to be cultured, civilised and wise by the knowledge, skills and values acquired. Le the pasi, education vyas informal and non-formal although during his period, Aristotle argued for the need of public education to sustain a democratic society. Plato talked of the just society and designed an education curriculum which was graded into several stages to achieve this goal and that of the philosopher king. From the Islamic perspective, knowledge ('ilm) means the arrival of the meaning of an object of knowledge in the soul or the arrival of the soul at the meaning of an object of knowledge (Al-Attas, 1993). Thus, through education one attains the meaning of life and existence. With knowledge, man will be able to put things in its proper place and thus be just to himself, others and to his Creator. He will also be able to act rightfully and thus be disciplined. He will act rightfully not only in terms of his conduct of this world but also of the " other" . Thus, education is the means to arrive at wisdom which leads to justice.